Complete Genome Sequence of Corynebacterium imitans DSM 44264, Isolated from a Five-Month-Old Boy with Suspected Pharyngeal Diphtheria - Möllmann, Sabrina (Genome Announc, 2014)
The complete genome sequence of the type strain Corynebacterium imitans DSM 44264 comprises 2,565,321 bp with a mean G+C content of 64.26%. The detection of the antibiotic resistance genes erm(X), aphA1-IAB, strA-strB, and cmx is fully consistent with the previously observed multidrug-resistant pattern of C. imitans isolates.